Synaptogenesis based bio-inspired NoC fault tolerant interconnects - Sethi, M.A.J. (2013)
Network on Chip (NoC) is a communication framework for interconnection of processing element (PE's). The excessive and parallel communication requirements of heterogeneous PE's in NoC have made the communication structure very complex. The size of the devices are scaled down to support the complexity but the size of interconnects remains the same. To support the complexity of NoC many fault tolerant routing techniques have been proposed to cope with the faulty nodes and interconnects which occur during the communication. All the routing algorithms lack the adaptiveness, robustness and they also have the drawbacks of congestion, delayed communication and latency issues. In this paper a synaptogenesis bases bio-inspired algorithm is proposed for NoC. This algorithm is fault tolerant as it adapts the mechanism of biological brain. The results show that the bio-inspired algorithm quickly recovers from the fault and it is robust and fault tolerant. The average packet network latency was increased by 11.64, average bandwidth was reduced by 0.07 and throughput is drop to 43.30 during the network recovery from faults. While comparing with literature technique the average throughput and accepted traffic is increased by 76.92. Â© 2013 IEEE.